Degradation of 14C-atrazine in soil under outdoor conditions - Queiroz, Brigida Pimentel Villar de; Monteiro, Regina Teresa Rosim (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate the mineralization rate and residue formation in a common soil type intensively used for agriculture in São Paulo, SP, Brazil. Atrazine 14C-ring-U-R was applied to a typic Hapludox Brazilian soil (5 L ha-1 or 2 mg kg-1 of a.i.). After this procedure, samples (200 g, dry weight basis) of this soil, with moisture adjusted to 2/3 of the field capacity, were distributed in erlenmeyer flasks. The flasks were incubated buried at CENA-USP Lysimeter Station, in a started jointly corn plantation. The evolved 14CO2 was analyzed every 15 day, during a period of 150 days. The desorbed residues were extracted with 0.01M CaCl2 solution and further extracted with the organic solvent, acetonitrile-water, 80:20, and the non-extractable residues were analysed by combustion. At the end of the incubation period (150 days), the 14CO2 evolved reached up to 36% of applied activity, and half-life of 168 days. The extractable residues decreased by 1/3 during the incubation period, while the non-extractable remained unchanged, around 34% of applied activity. TLC analyses of desorbed fraction showed hydroxiatrazine (44%), deisopropylatrazine (3.28%) and atrazine (52.72%) whereas the extracted fraction presented hydroxyatrazine (16.22%), deisopropylatrazine (2.25%), desethylatrazine (2.24%), and atrazine (79.29%). It was concluded that only the extractable fraction of residues was mineralized and that variation of the incubation temperature favored atrazine mineralization.